Про використання моделей пульсацiй тиску на плоскiй стiнцi для опису пульсацiй тиску на поверхнях цилiндричних конструкцiй - Борисюк, А.О. (Видавничий дім "Академперіодика" НАН України, 2007)
Conditions are searched, under which the available models of pressure fluctuations on a flat wall (i. e., the models of Crocos, Chase, F. Williams, and Smol'yakov and Tkachenko) can be used to describe the pressure fluctuation field which arises on the surfaces of cylindrical structures under their interaction with fully developed turbulent flows of incompressible fluids. For this purpose, the appropriate method and experimental equipment are developed. As a result, it is found that, in case of the axial symmetry of a flow, the acceptable-far-practice results of calculations of the vibration and/or acoustic fields of cylindrical structures can be obtained in the frames of the Chase model. This allows one to recommend the use of the model for description of the pressure field noted above. In case of a non-axisymmetric flow, the application of all the models of pressure fluctuations on a flat wall is unreasonable.